Bolesław Prus and the Jews - Friedrich, Agnieszka (Jews of Poland., 2021)
"Bolesław Prus and the Jews shows the complexity of the so-called "Jewish question" in nineteenth-century Congress Poland and especially its significance in Prus' social concept reflected in his extensive body of journalistic work, fiction, and treatises. The book traces Prus' evolving worldview toward Jews, from his support of the Assimilation Program in his early years to his eventual support of Zionism. These contrasting ideas show us the complexity of the discourse on Jewish issues from the individual perspective of a significant writer of the time, as well as the dynamics of the Jewish modernization process in a "non-existent" partitioned Poland. The portrait of Prus that emerges is surprisingly ambivalent"--